2020
DOI: 10.35595/2414-9179-2020-2-26-436-442
|View full text |Cite
|
Sign up to set email alerts
|

Structural interpretation of lineaments using satellite image processing: A case study in the vicinity of the Charvak reservoir

Abstract: This work presents the results of lineaments interpretation using the automated method of the satellite images in the territory of the Charvak water reservoir in Uzbekistan. Tectonic and local (water impoundment in Charvak reservoir) features of the region deformation were determined on base LINE algorithm in software PCI Geomatica. The thematic map with the geospatial arrangement of lineaments was constructed on base of satellite images LANDSAT-8 processing. We concluded that water level fluctuations have a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…To verify the results obtained, the extracted lineament structures are compared with the lineaments obtained by hand digitizing from geological maps [2]. The work presents a processing method using multi-temporal Landsat 8 imageries were determined on base LINE algorithm in software PCI Geomatica in the territory of the water reservoir [3]. The result showed that water level fluctuations have a greater influence on the appearance of the lineaments structure than periods of water filling and downstream in the reservoir.…”
Section: Statistical Analysis Of Lineaments Using Landsat 8 Data: a Case Study Of The Fergana Valley (East Uzbekistan)mentioning
confidence: 99%
“…To verify the results obtained, the extracted lineament structures are compared with the lineaments obtained by hand digitizing from geological maps [2]. The work presents a processing method using multi-temporal Landsat 8 imageries were determined on base LINE algorithm in software PCI Geomatica in the territory of the water reservoir [3]. The result showed that water level fluctuations have a greater influence on the appearance of the lineaments structure than periods of water filling and downstream in the reservoir.…”
Section: Statistical Analysis Of Lineaments Using Landsat 8 Data: a Case Study Of The Fergana Valley (East Uzbekistan)mentioning
confidence: 99%
“…Plastic waste can be most clearly distinguished from the surrounding sea in the near-infrared (NIR) and short-wave infrared (SWIR) bands, in which is particularly sensitive to the wavelength range around 1215 nm and 1732 nm [Biermann et al, 2020;Ciappa, 2021]. Themistocleous et al (2020) analyzed the spectral reflectance characteristics of plastic waste on Sentinel 2 satellite images, in which the plastic fragments have a much higher reflectivity than the surrounding seawater, especially from the red to NIR wavelength [Themistocleous et al, 2020]. Kikaki et al (2020) used multiple remote sensing data sources, including 400 Planet high spatial resolution optical satellite images (spatial resolution from 3 to 5 m), 340 Sentinel 2 images (spatial resolution up to 10 m), 125 Landsat 8 images (30 m spatial resolution) and in situ data to create a plastic pollution map in the Caribbean and Motagua estuary (Honduras) [Kikaki et al, 2020].…”
Section: Introductionmentioning
confidence: 99%
“…Since the difference in spectral reflectance values between floating plastic waste and seawater is not large, it is very difficult to detect and classify marine plastic waste from optical satellite image bands. To overcome this limitation, Biermann et al (2020) proposed a Floating Debris Index (FDI) using red (band 4), NIR (band 8), Red Edge 2 (band 6) and SWIR1 (band 11) of Sentinel2 imagery. To improve the accuracy in classifying ocean plastic waste, the authors used a combination of FDI and NDVI, NDWI indices to eliminate the effects of seawater and plants on plastic waste [Biermann et al, 2020].…”
Section: Introductionmentioning
confidence: 99%